Early Childhood Learning Quality in Pandalungan Community - Nur Atika, Aisyah; Khutobah; Misno; Haidor; Ariefianto, Lutfi; Syarifudin (Program Studi Magister Pendidikan Anak Usia Dini, 2019)
The challenge for rural communities to provide quality education for early childhood in Indonesia is difficult. National politics, policies, and economic and cultural conditions affect the Early Childhood Education system, and Indonesia is a large multicultural country, so, even the quality of education is difficult. This study aims to look at the quality of children's education in Pandalungan. Using qualitative methods with ethnographic design, data collection techniques using interviews, observation, and documentation. The results showed that educational institutions for children in urban areas can be categorized quite high. However, for early childhood education services in Desa Sukorambi Pandalungan, the quality is quite poor. Research suggestions are the need for follow-up related to social, economic, cultural and environmental factors at the level of Pandalungan community awareness of early childhood education. Keywords: Early Childhood, Learning Quality, Pandalungan Community References: Bernal, R., & Ramírez, S. M. (2019). Improving the quality of early childhood care at scale: The effects of “From Zero to Forever.” World Development, 118, 91–105. https://doi.org/10.1016/j.worlddev.2019.02.012 Bers, M. U., González-González, C., & Armas-Torres, M. B. (2019). Coding as a playground: Promoting positive learning experiences in childhood classrooms. Computers and Education, 138, 130–145. https://doi.org/10.1016/j.compedu.2019.04.013 Biersteker, L., Dawes, A., Hendricks, L., & Tredoux, C. (2016). Center-based early childhood care and education program quality: A South African study. Early Childhood Research Quarterly, 36, 334–344. https://doi.org/10.1016/j.ecresq.2016.01.004 Burchinal, M. (2018). Measuring Early Care and Education Quality. Child Development Perspectives, 12(1), 3–9. https://doi.org/10.1111/cdep.12260 Church, A., & Bateman, A. (2019). Methodology and professional development: Conversation Analytic Role-play Method (CARM) for early childhood education. Journal of Pragmatics, 143(xxxx), 242–254. https://doi.org/10.1016/j.pragma.2019.01.022 Ciolan, L. E. (2013). Play to Learn, Learn to Play. Creating Better Opportunities for Learning in Early Childhood. Procedia - Social and Behavioral Sciences, 76, 186–189. https://doi.org/10.1016/j.sbspro.2013.04.096 Correia, N., Camilo, C., Aguiar, C., & Amaro, F. (2019). Children’s right to participate in early childhood education settings: A systematic review. Children and Youth Services Review, 100, 76–88. https://doi.org/10.1016/j.childyouth.2019.02.031 Cycyk, L. M., & Hammer, C. S. (2018). Beliefs, values, and practices of Mexican immigrant families towards language and learning in toddlerhood: Setting the foundation for early childhood education. Early Childhood Research Quarterly. https://doi.org/10.1016/j.ecresq.2018.09.009 Dick, C. & C. (2009). The Sistematic Design Of Instruction. New Jersey: Upper Saddle River. Grindal, T., Bowne, J. B., Yoshikawa, H., Schindler, H. S., Duncan, G. J., Magnuson, K., & Shonkoff, J. P. (2016). The added impact of parenting education in early childhood education programs: A meta-analysis. Children and Youth Services Review, 70, 238–249. https://doi.org/10.1016/j.childyouth.2016.09.018 Herbers, J. E., Cutuli, J. J., Jacobs, E. L., Tabachnick, A. R., & Kichline, T. (2019). Early childhood risk and later adaptation: A person-centered approach using latent profiles. Journal of Applied Developmental Psychology, 62(January), 66–76. https://doi.org/10.1016/j.appdev.2019.01.003 Hunkin, E. (2018). Whose quality? The (mis)uses of quality reform in early childhood and education policy. Journal of Education Policy, 33(4), 443–456. https://doi.org/10.1080/02680939.2017.1352032 Johson, J. E, & Roopnarine, J. L. (2011). Pendidikan anak usia dini dalam berbagai pendekatan. Jakarta: Kencana Prenada Media Group. Lucas, F. M. M. (2017). The Game as an Early Childhood Learning Resource for Intercultural Education. Procedia - Social and Behavioral Sciences, 237(June 2016), 908–913. https://doi.org/10.1016/j.sbspro.2017.02.127 Atwi Suparman. (2012). Desain Intruksional Modern. Jakarta: Erlangga. Mapiare, A. (2013). Tipe-tipe Metode Riset Kualitatif Untuk Eksplanasi Sosial Budaya Dan Bimbingan Konseling. Malang: Elang Emas & Prodi Bimbingan Dan Konseling Fakultas Ilmu Pendidikan Universitas Negeri Malang. Milner, K. M., Bhopal, S., Black, M., Dua, T., Gladstone, M., Hamadani, J., … Lawn, J. E. (2019). Counting outcomes, coverage and quality for early child development programmes. Archives of Disease in Childhood, 104, S3–S12. https://doi.org/10.1136/archdischild-2018-315430 Morrison, G. S. (2012). Dasar-dasar Pendidikan Anak Usia Dini. Jakarta: Indeks. Nutbrown, C. (2011). Key Concepts in Early Childhood Education and Care (2nd ed.). London: SAGE Publication Ltd. Perpres. Pelaksanaan Pencapaian Tujuan Pembangunan Berkelanjutan. , 6 Peraturan Presiden RI § (2017). Puspita, W. A. (2013). Multikulturalisme dalam Pendidikan Anak Usia Dini. Jurnal Ilmiah VISI P2TK PAUDNI, 8(2), 144–152. Raikes, A., Sayre, R., Davis, D., Anderson, K., Hyson, M., Seminario, E., & Burton, A. (2019). The Measuring Early Learning Quality & Outcomes initiative: purpose, process and results. Early Years, 39(4), 360–375. https://doi.org/10.1080/09575146.2019.1669142 Satrio Roefandi, P. (2019). Keluarga Pendalungan, Keluarga Berbasis Budaya Madura Atau Jawa? 10 Th Psychofest Conference, (March), 316–324. https://doi.org/10.31227/osf.io/v8g5b Stokoe, E. (2014). The Conversation Analytic Role-play Method (CARM): a method for training communication skills as an alternative to simulated role-play. Res. Lang. Soc. Interact, 47(3), 255–265. Sutarto, A. (2006). Sekilas Tentang Masyarakat Pandalungan. Jelajah Budaya 2006, 1–7. Suyadi. (2010). Psikologi Pendidikan Anak Usia Dini. Yogyakarta: Pustaka Insan Madani. Tapscott, D. (2011). Grown Up Digital: How the Net Generation Is Changing Your World. Bucharest: Publica. Wijana, W. D. (2014). Konsep-Konsep Dasar Pendidikan Anak Usia Dini. In UT. https://doi.org/10.1101/112268 Yoshikawa, H., Wuermli, A. J., Raikes, A., Kim, S., & Kabay, S. B. (2018). Toward High-Quality Early Childhood Development Programs and Policies at National Scale: Directions for Research in Global Contexts. Social Policy Report,31(1), 1–36. https://doi.org/10.1002/j.2379-3988.2018.tb00091.x